Treatment pattern and response for cluster headache in Korea: A prospective multicenter observation study. (April 2023) - Lee, Mi Ji; Park, Jeong Wook; Chu, Min Kyung; Moon, Heui-Soo; Chung, Pil-Wook; Chung, Jae Myun; Sohn, Jong-Hee; Kim, Byung-Kun; Kim, Byung-Su; Kim, Soo-Kyoung; Song, Tae-Jin; Choi, Yun-Ju; et al.
Background: Only limited data are available regarding the treatment status and response to cluster headache in an Asian population. Therefore, this study aimed to provide a real-world treatment pattern of cluster headache and the response rate of each treatment in an Asian population. Methods: Patients with cluster headache were recruited between September 2016 and January 2019 from 16 hospitals in Korea. At the baseline visit, we surveyed the patients about their previous experience of cluster headache treatment, and acute and/or preventive treatments were prescribed at the physician's discretion. Treatment response was prospectively evaluated using a structured case-report form at 2 ± 2 weeks after baseline visit and reassessed after three months. Results: Among 295 recruited patients, 262 experiencing active bouts were included. Only one-third of patients reported a previous experience of evidence-based treatment. At the baseline visit, oral triptans (73.4%), verapamil (68.3%), and systemic steroids (55.6%) were the three most common treatments prescribed by the investigators. Most treatments were given as combination. For acute treatment, oral triptans and oxygen were effective in 90.1% and 86.8% of the patients, respectively; for preventive treatment, evidence-based treatments, i.e. monotherapy or different combinations of verapamil, lithium, systemic steroids, and suboccipital steroid injection, helped 75.0% to 91.8% of patients. Conclusion: Our data provide the first prospective analysis of treatment responses in an Asian population with cluster headache. The patients responded well to treatment despite the limited availability of treatment options, and this might be attributed at least in part by combination of medications. Most patients were previously undertreated, suggesting a need to raise awareness of cluster headache among primary physicians.